Beyond αβ T cells: NK, iNKT, and γδT cell biology in leukemic patients and potential for off-the-shelf adoptive cell therapies for AML - Kent, Andrew; Crump, Lyndsey S.; Davila, Eduardo (Frontiers in Immunology, 2023)
Acute myeloid leukemia (AML) remains an elusive disease to treat, let alone cure, even after highly intensive therapies such as stem cell transplants. Adoptive cell therapeutic strategies based on conventional alpha beta (T cells are an active area of research in myeloid neoplasms given their remarkable success in other hematologic malignancies, particularly B-cell-derived acute lymphoid leukemia, myeloma, and lymphomas. Several limitations have hindered clinical application of adoptive cell therapies in AML including lack of leukemia-specific antigens, on-target-off-leukemic toxicity, immunosuppressive microenvironments, and leukemic stem cell populations elusive to immune recognition and destruction. While there are promising T cell-based therapies including chimeric antigen receptor (CAR)-T designs under development, other cytotoxic lymphocyte cell subsets have unique phenotypes and capabilities that might be of additional benefit in AML treatment. Of particular interest are the natural killer (NK) and unconventional T cells known as invariant natural killer T (iNKT) and gamma delta (T cells. NK, iNKT, and T cells exhibit intrinsic anti-malignant properties, potential for alloreactivity, and human leukocyte-antigen (HLA)-independent function. Here we review the biology of each of these unconventional cytotoxic lymphocyte cell types and compare and contrast their strengths and limitations as the basis for adoptive cell therapies for AML.